Geometric analyses of changes in nasal septum deviation following maxillary expansion - AlShemali, Ahmad; Knigge, Ryan P; Motro, Melih; Parsi, Goli K; Sherwood, Richard J; McNulty, Kieran P; Will, Leslie A (European journal of orthodontics, 2025)
Abstract Objectives Maxillary transverse discrepancies are routinely addressed by palatal expansion. Nasal septum deviation is suspected to be related to these discrepancies. Current evidence using linear and angular measurements from two-dimensional radiographs on the effect of rapid palatal expansion on the nasal septum is not conclusive. The objective of this study was to apply three-dimensional geometric morphometric analyses to cone-beam computed tomography scans of the nasal septum to investigate changes in response to palatal expansion. Methods Cone-beam computed tomography scans of the nasal septa of 71 subjects (53, expansion and 18, control) from 2 timepoints were segmented on using Mimics™ software. Anatomical landmarks and semilandmarks were digitized using Checkpoint™. Differences in septal deviation between the two timepoints were tested. Generalized Procrustes analysis and principal component analysis assessed overall shape differences and pattern variance in the septum. Least square regression was used to test for correlations. Heat maps visualized which areas exhibited the greatest amount of change. Results In the control group, none of the septum deviation variables changed significantly between the timepoints, while all were significantly different for the expansion group. Heatmaps showed greater increase in interlandmark distances for the expansion group compared with the controls, with the posterosuperior part of the septum bearing the greatest change and the central, inferior part showing the least change. Conclusion Findings suggest that the septum does not straighten during expansion but continues to deviate with age.